Defluoridation of drinking water using a new flow column-electrocoagulation reactor (FCER) - Experimental, statistical, and economic approach. (15th July 2017) - Hashim, Khalid S.; Shaw, Andy; Al Khaddar, Rafid; Ortoneda Pedrola, Montserrat; Phipps, David
Abstract: A new batch, flow column electrocoagulation reactor (FCER) that utilises a perforated plate flow column as a mixer has been used to remove fluoride from drinking water. A comprehensive study has been carried out to assess its performance. The efficiency of fluoride removal (R%) as a function of key operational parameters such as initial pH, detention time (t), current density (CD), inter-electrode distance (ID) and initial concentration (C0 ) has been examined and an empirical model has been developed. A scanning electron microscopy (SEM) investigation of the influence of the EC process on morphology of the surface of the aluminium electrodes, showed the erosion caused by aluminium loss. A preliminary estimation of the reactor's operating cost is suggested, allowing for the energy from recycling of hydrogen gas hydrogen gas produced amount. The results obtained showed that 98% of fluoride was removed within 25 min of electrolysis at pH of 6, ID of 5 mm, and CD of 2 mA/cm 2 . The general relationship between fluoride removal and operating parameters could be described by a linear model with R 2 of 0.823. The contribution of the operating parameters to the suggested model followed the order: t > CD > C0 > ID > pH. The SEM images obtained showed that, after the EC process, the surface of the anodes, became non-uniform with a large number of irregularities due to the generation of aluminium hydroxides. It is suggested that these do not materially affect the performance. A provisional estimate of the operating cost was 0.379 US /m 3 . Additionally, it has been found that 0.6 kW/m 3 is potentially recoverable from the H2 gas. Graphical abstract: Fluoride removal at different initial concentrations. Highlights: The new reactor, FCER, removed 98% of fluoride. Performance of FECR, in terms of fluoride removal, was modelled with R 2 of 0.823. FCER emits H2 gas enough to produce energy of 0.6 kW/m 3 . SEM images showed many dents on the anode due to the production of Al hydroxides. FCER required 0.379 US /m 3 to remove 20 mg/L of fluoride from drinking water.